Analysis Of The Influence Of The Quality Of Ponek Emergency Room Service Quality On Patient Satisfaction At Pulang Pisau Hospital - Sandra, Santi; Vip Paramarta; ⁠Eka Purwanda (Sean Institute, 2024)
This study aims to analyze the influence of service quality IGD PONEK (Comprehensive Emergency Neonatal Obstetrics Services) on patient satisfaction at Pulang Pisau Hospital. The quality of service in emergency services, especially in the PONEK unit, is very important because it is directly related to the safety of mothers and babies. A survey was conducted on patients and their families who received PONEK emergency room services at Pulang Pisau Hospital. The dimensions of service quality analyzed include service speed, competence of medical personnel, facilities, and responsiveness to emergency conditions. The results showed that the quality of service quality had a significant influence on the level of patient satisfaction. Aspects of officer competence and responsiveness are the main factors that affect satisfaction, while facilities still need to be improved. This study provides recommendations for hospitals to improve aspects of facilities to increase overall patient satisfaction.